The establishment of LAPS SJK in the trajectory of history viewed from the politics of Indonesian law - Setiyono, Setiyono; Keumala, Dinda; Sabirin, Ahmad; Rahmat, Nur Ezan; Suzaini, Syaqila Binte; Bayuaji, Anandayu Pavita (Universitas Ahmad Dahlan, 2024)
Introduction to the Problem: The history of the formation of the LAPS SJK is based on the importance of consumer protection in the financial services sector. According to the law concerning the role of the Financial Service Authority, the institution is given the authority to facilitate the settlement of complaints from consumers who are harmed by the finance actors. The OJK then issued regulation (POJK) Number 1/POJK.07/2014 concerning Alternative Dispute Resolution Institutions in the Financial Services Sector (LAPS SJK) which was later replaced by regulation Number 61/POJK.07/2020.Purpose/Objective Study: This research examines, how is the history of the LAPS SJK formation and how is the legal politics of the formation.Design/methodology/Approach: This research is normative, using a historical approach. It applies a descriptive method with the secondary data.Findings: The interesting finding is that the establishment of LAPS SJK is to protect consumers in the event of a dispute with the financial actors, so the legal politics regulating the LASP SJK should be an integrated part of the political scheme of consumer protection law. Institutionally, the legal politics of establishing LAPS SJK is motivated by 3 (three) reasons. The initial reason is the establishment of OJK which has a determinant role and function to supervise integrated financial services business activities for the capital market, banking, and non-banking sectors. Another reason is the reality of the advanced development of technology in the global financial services sector, and the last reason is the need of the parties involved in the financial services sector industry; both consumers and finance actors who need an ideal non-court dispute resolution institution.Paper Type: Research Article